Individual Behavior and Collective Action: The Path to Iceland's Financial Collapse - Thorvaldur Gylfason; Gylfi Zoega (Center for Economic Studies and ifo Institute (CESifo), 2019)
Unsustainable accumulation of debt precedes financial crises. The recent Western financial crisis was no exception in this regard. The external debt of Greece, Iceland, Ireland, and Spain increased exponentially, in Iceland at a rate higher than the rate of interest on foreign debt. The Ponzi scheme that played out in Iceland begs the question why a country would set out on a path that could lead to a financial crisis. We address this question and describe the private incentives faced by bankers, financiers, politicians and others. In particular, we show how private incentives and a culture that valued financial gains above all else collided with socially desirable outcomes. The root of the problem in Iceland as well as in other crisis countries was a failure at the state level to align private incentives with what was socially prudent, a failure due, at least in Iceland, to a combination of mistakes, incompetence and what can only be called corruption. Furthermore, misplaced belief in a market economy where morals and ethics play no role paved the way to serious lapses in accounting and in the operation of the banks.
Keywords: E44; G01; G41; 330; financial crises; corruption; culture; Iceland; quality of governance; rent seeking